First isolation of hirame rhabdovirus from freshwater fish in Europe. Issue 5 (21st August 2013) - Borzym, E; Matras, M; Maj‐Paluch, J; Baud, M; De, C; Talbi, C; Olesen, N J; Bigarré, L
Abstract A rhabdovirus was isolated in cell culture inoculated with tissue material from diseased grayling, Thymallus thymallus (L.), originating from a fish farm affected by a mortality episode in Poland. Diagnostics tests showed that the virus was not related to novirhabdoviruses known in Europe, nor to vesiculovirus‐like species, except perch rhabdovirus (PRhV) with which it shared moderate serological relations. However, RT‐PCR with PRhV probes gave negative results. To identify the virus, a random‐priming sequence‐independent single primer amplification was adopted. Surprisingly, two of the obtained sequences exhibited a high identity (>99%) with hirame rhabdovirus (HIRRV), a novirhabdovirus usually found in fish in marine Asiatic countries, for instance Japan, China and Korea. The full‐length sequence of the phosphoprotein gene (P) demonstrated a higher identity of the present isolate with HIRRV from China compared with the Korean isolate. An identical viral sequence was also found in brown trout, Salmo trutta trutta L., affected by mortalities in a second farm in the same region, after a likely contamination from the grayling farm. To our knowledge, this is the first report of HIRRV in Europe, and in two hosts from fresh water that have not been described before as susceptible species.